Legal Liability of Business Actors Who Advertise Defective Products to Consumers - Maria Cristina (Mahesa Research Center, 2023)
This research aims to discuss consumer protection in the relationship between business actors and consumers, specifically focusing on the legal liability of businesses that advertise defective products to consumers. The research method used is the normative doctrinal method with an analytical descriptive approach. Primary and secondary data are obtained through literature study and analysis of applicable laws and regulations. The results show that consumers have an important role as end users of products and services offered by businesses. However, consumers' negotiating power is limited due to product complexity, false information, and power imbalances. Legal protection is needed to safeguard consumers who are in a vulnerable position. Consumer protection laws in Indonesia, such as the Consumer Protection Law (UUPK), aim to increase consumers' understanding and awareness of their rights. Therefore, consumer protection needs to be strengthened through education, training, and the implementation of clear regulations.